The Jalateh Tradition as a Medium of Tulak Bala in the Community of Sawang District, South Aceh Regency: Tradisi Jalateh sebagai Media Tulak Bala pada Masyarakat Kecamatan Sawang Kabupaten Aceh Selatan - Husda, Husaini; Susan Fariaton; Idria, Reza; Razak, Abd (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2026)
This study examines the Jalateh tradition as a medium of tulak bala (warding off misfortune) in the community of Sawang District, South Aceh Regency. The Jalateh tradition is a form of local wisdom carried out annually during the month of Safar, especially on the last Wednesday night (Rabu abeh), as a communal effort to seek protection from diseases and disasters. This research employs a qualitative method with an inductive approach through observation, interviews, and documentation. The findings reveal that the Jalateh tradition is performed by walking around the village while reciting the Ya Latif prayer, shalawat, and verses of the Qur’an led by the teungku imum, followed by a communal prayer gathering near the river. This tradition not only functions as a religious practice to seek safety and protection from Allah SWT but also serves to strengthen social solidarity and preserve the cultural identity of the community. The existence of the Jalateh tradition reflects the integration of adat, culture, and Islamic values in the life of the South Acehnese society.